1987
DOI: 10.1111/j.1365-2885.1987.tb00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Florfenicol in non‐lactating dairy cows: pharmacokinetics, binding to plasma proteins, and effects on phagocytosis by blood neutrophils

Abstract: Serial blood samples were collected and plasma concentrations of florfenicol (FLO) were measured following the administration of an intravenous bolus of 50 mg/kg FLO to five healthy non-lactating dairy cows. A triexponential equation provided the best fit of the data for four of the five cows. The mean value for beta corresponded to a half-life of 3.2 h. The mean apparent volume of distribution was 0.67 l/kg, and the mean body clearance was 0.15 l/kg/h. The extent of binding of FLO to bovine plasma proteins wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
52
3

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 13 publications
(11 reference statements)
8
52
3
Order By: Relevance
“…The Cl T was similar to that reported for thiamphenicol in dogs (Castells et al 1998). Bretzlaff et al (1987) suggested that the small Cl of florfenicol in animals is due to the replacement of -OH in chloramphenicol and thiamphenicol by -F in the structure florfenicol, which thereby prevents the conjugation with glucuronic acid and delays its excretion. These little differences may be related to differences in metabolism, analytical methods or the metabolic body size of the animals under study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The Cl T was similar to that reported for thiamphenicol in dogs (Castells et al 1998). Bretzlaff et al (1987) suggested that the small Cl of florfenicol in animals is due to the replacement of -OH in chloramphenicol and thiamphenicol by -F in the structure florfenicol, which thereby prevents the conjugation with glucuronic acid and delays its excretion. These little differences may be related to differences in metabolism, analytical methods or the metabolic body size of the animals under study.…”
Section: Discussionsupporting
confidence: 82%
“…The minimum inhibitory concentrations (MICs) of florfenicol for bacterial isolates from dogs have not yet been determined. Based on the MIC data for bacteria from fish, swine, calves and cows, 1-2 µg/ml florfenicol showed high efficacy against most bacteria (Varma et al 1986;Bretzlaff et al 1987;Ueda et al 1995;Ho et al 2000). In this study, the time of plasma concentration above 1 µg/ml was approximately 8 h. Therefore, florfenicol should be given twice daily at a dosage of 30 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Bretzlaff et al (1987) reported a suppressive effect of florfenicol on the activity of neutrophiles. They observed that florfenicol at concentrations within the ranges of 5 to1000 μg/ml of cell culture inhibited phagocytosis of 32 phosphorus-labelled Staphylococcus aureus by bovine blood neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Afifi et al (1997) found higher concentrations in the lung,liver, kidney, muscle and plasma than that in brain and fat of the broiler following singledose of 3Omg/kg by i.rn, and the FFC became undetectable at 72 h postdose in above tissues except in the bilefrom where it disappeared after 96 h (Afifi and Abo el-Sooud, 1997). Florfenicol appeared to have higher concentrations and AVC in the kidney as it dominated the excretion of florfenicol at a large extent (Varma et al, 1986;Bretzlaff et al, 1987). In most animal species, 80% of florfenicol was excreted from urine as parent drug while 11.2-17% as florfenicol amine, less than 10% as florfenicol oxamic alcohol and 1.1% as florfenicol alcohol according to its determination by radioisotope labellingin the residue report of EMEA (1999) (Committee for veterinary medicinal products, 1999).This metabolic characteristic was similar with thiamphenicol but totally different from CAP, the majority of which was excreted as its derivatives (Syriopoulou et al, 1981).…”
Section: Discussionmentioning
confidence: 99%